STATE IMPACT ON THE INTERNATIONALIZATION LEVEL OF HIGHER EDUCATION INSTITUTIONS: THE EXPERIENCE OF POLAND (Development Service Industry Management, 2024)
The internationalization of higher education is an important component of the strategy of many countries aimed at strengthening international cooperation, increasing the competitiveness of universities, and integrating scientific potential into the global educational space. The examples of EU countries testify to the importance of having national strategic documents that define long-term goals and directions for the development of the internationalization of science and education. Poland also faces the task of developing a national internationalization strategy based on the state scientific policy and the corresponding legislative provision. It is expected that such a strategy will contribute to the integration of Polish universities into the international academic space and the development of science. A key indicator of internationalization is the number of foreign students in Polish universities, which reflects the ability of universities to integrate into global processes. The influence of the state on the attraction of foreigners is realized through the policies of financial support, visa liberalization and simplification of administrative procedures, the development of international educational programs and the popularization of Polish education abroad. Private universities demonstrate higher rates of internationalization due to their focus on foreign students. However, Polish visa policy needs improvement due to the abuse of easy access to study, when the real goal is to work or emigrate to other Schengen countries. In this regard, the Ministry of Foreign Affairs of Poland introduced changes in the visa system, including increasing requirements for candidates and limiting access to the labor market. An analytical review of the Polish experience shows the significant role of state support in achieving the goals of internationalization, which is a promising direction for further research in the field of educational policy.
Keywords: university; internationalization; number of students; visa policy; Poland